2009
DOI: 10.1080/10715760903089708
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of SERCA in the chronic phase of adjuvant arthritis as a possible adaptation mechanism of redox imbalance

Abstract: Adjuvant arthritis (AA) is a condition that involves systemic oxidative stress. Unexpectedly, it was found that sarcoplasmic reticulum Ca(2 +)-ATPase (SERCA) activity was elevated in muscles of rats with AA compared to controls, suggesting possible conformational changes in the enzyme. There was no alteration in the nucleotide binding site but rather in the transmembrane domain according to the tryptophan polar/non-polar fluorescence ratio. Higher relative expression of SERCA, higher content of nitrotyrosine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…As resulted also from our previous experiments (Bauerova et al, 2005a, 2005b, 2008a, 2008bDrafi et al, 2010;Jancinova et al, 2009;Kogan et al, 2005;Macickova et al, 2010;Ponist et al, 2010;Sotnikova et al, 2009;Strosova et al, 2008Strosova et al, , 2009), all performed in the AA model, substances with antioxidant properties have a high potency to be used in therapy of RA. They decreased the progression of AA when administered to rats with AA over the period of 28 days.…”
Section: Newer Experimental Therapies With Antioxidants Evaluated In Aamentioning
confidence: 58%
See 2 more Smart Citations
“…As resulted also from our previous experiments (Bauerova et al, 2005a, 2005b, 2008a, 2008bDrafi et al, 2010;Jancinova et al, 2009;Kogan et al, 2005;Macickova et al, 2010;Ponist et al, 2010;Sotnikova et al, 2009;Strosova et al, 2008Strosova et al, , 2009), all performed in the AA model, substances with antioxidant properties have a high potency to be used in therapy of RA. They decreased the progression of AA when administered to rats with AA over the period of 28 days.…”
Section: Newer Experimental Therapies With Antioxidants Evaluated In Aamentioning
confidence: 58%
“…Clinical studies have shown increased plasmatic levels of MDA in patients with RA (Baskol et al, 2005(Baskol et al, , 2006Sarban et al, 2005). The level of MDA in the plasma of arthritic animals was also elevated (Bauerova et al, 2008bHe et al, 2006;Sotnikova et al, 2009;Strosova et al, 2008Strosova et al, , 2009Tastekin et al, 2007). In recent years, methods based on chemiluminescence and fluorescence measurements have been widely used for determination of ROS, RNS and lipid peroxidation metabolites.…”
Section: Adjuvant Arthritis: An Animal Model For Preclinical Evaluatimentioning
confidence: 99%
See 1 more Smart Citation
“…Bauerova and Bezek (1999) and Jaswal et al (2003) described oxidative stress as a primary factor involved in the RA pathogenetic changes. Our previous results with different antioxidants and immunomodulators showed a beneficial effect of these substances on the development of adjuvant arthritis (AA) (Bauerova et al , 2005a, 2005b 2008a, 2008b 2009, 2011, Drabikova et al , 2009; Drafi et al , 2010; Jancinova et al , 2009; Kogan et al , 2005; Macickova et al , 2010; Ponist et al , 2010; Sotnikova et al , 2009; Strosova et al , 2008, 2009). The advantage of AA as an experimental arthritis model is its great similarity to RA, such as symmetrical joint involvement, persistent joint inflammation, synovial hyperplasia, and a good response to most therapies effective in RA (Bina & Wilder, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in SOD induced the scavenging of the superoxide ione into H 2 O 2 , a more potent reactive oxygen species, which may be accumulated due to a reduction in GPx resulting in increased lipid peroxidation which is reflected in the significant increase in MDA in the present study. Adjuvant arthritis is a condition that involves systemic oxidative stress (Strosova et al, 2009), which could be reflected by an elevation in SOD and a reduction in GPx levels in the present study, together with the reduction in TAC and increased MDA. The elevation in the plasma levels of MDA in the arthritic control rats in the current research is in agreement with the results of Tastekin et al (2007).…”
Section: Discussionmentioning
confidence: 67%